Sleep problems: an emerging public health issue. - H. S., Siddalingaiah (International Journal Of Community Medicine And Public Health, 2017)
Sleep is one of the most significant yet neglected topic by health professionals as well as general public. Sleep has profound implications for physical, mental and psychological wellbeing of an individual. Modern socio-economic and lifestyle factors have resulted in sudden increase of the prevalence of sleep disorders over last few decades. Sleep disorders are resulting in significant economic losses for nations and are becoming a public health burden. High quality research studies have helped to better understand the determinants of sleep problems. Also the understanding of the nature and the control mechanisms of sleep have helped in devising screening, preventive and early-intervention modalities which need to be utilized widely by clinical and public health professionals. Advocating and educating about optimal sleep quantity, quality and sleep hygiene at occupational, institutional and various high risk group settings should be done by public health professionals through regulation on work hours, work shift patterns, and behaviour modification measures.